Innovations in Financing Food Security - Gilberto M. Llanto; Jocelyn Alma R. Badiola (Philippine Institute for Development Studies (PIDS), 2010)
A recent publication of the UN Food and Agricultural Organization (FAO) has highlighted the food insecurity problem facing the globe: food production will have to increase by 70 percent in 2050 to keep up with a global population that is projected to grow from 6 billion to 9 billion. There has to be more investments in agriculture to improve productivity, which will be critical to the goal of achieving food security. There is scope for governments and the private sector cooperation in food production. The paper discusses innovative financing schemes geared to food production and identifies policy gaps, that is, areas where governments could intervene to enhance the workings of the market.
Keywords: 330; Philippines; innovative financing schemes; food insecurity; value chain financing; covariant risks; risk management tools; index-based insurance; warehouse receipts lending; trade finance; Ernährungssicherung; Agrarproduktion; Technischer Fortschritt; Agrarpolitik; Welt